Optimization of Kurikulum Merdeka through differentiated learning: Effectiveness and implementation strategy - Umi Nahdhiah; Oktaviani Adhi Suciptaningsih (Inovasi Kurikulum, 2024)
The implementation of Kurikulum Merdeka presents differentiated learning. Some challenges in implementing differentiated learning are teachers' expertise and insufficient resources. Moreover, the execution of Kurikulum Merdeka at all education levels often perplexes many teachers. Meanwhile, the literature findings indicate that there is still minimal research related to differentiated learning, emphasizing the need for studies on the impact of differentiated approaches. This study aims to explain the implementation strategy of differentiated learning and review its effectiveness in learning Kurikulum Merdeka. This research uses a qualitative descriptive approach with a literature review method. Data is obtained from articles and publications that align with the writing topic. The finding of this study is that differentiation learning is implemented through the differentiation of content, processes, products, and environments. Differentiated teaching, assessment, and learning activities should accommodate diverse student learning styles, interests, and readiness levels. Differentiated learning can be effectively applied to learning. Differentiated learning has a positive effect on learning in terms of learning outcomes and learning processes. Differentiated learning can improve student academic achievement, positively affecting student motivation, participation, independence, learning concentration, self-confidence, and understanding of the material. AbstrakImplementasi kurikulum merdeka menghadirkan pembelajaran berdiferensiasi. Beberapa tantangan dalam penerapan pembelajaran berdiferensiasi adalah keahlian guru dan keterbatasan sumber daya. Terlebih lagi, penerapan Kurikulum Merdeka di semua jenjang pendidikan seringkali membingungkan banyak guru. Sementara itu, temuan literatur menunjukkan masih minimnya penelitian terkait pembelajaran berdiferensiasi, sehingga menekankan perlunya kajian mengenai dampak pendekatan berdiferensiasi. Tujuan penelitian ini ialah menjelaskan bagaimana strategi implementasi pembelajaran berdiferensiasi dan meninjau efektivitasnya dalam pembelajaran Kurikulum Merdeka. Penelitian ini memakai pendekatan deskriptif kualitatif dengan metode literature review. Data diperoleh dari artikel maupun publikasi lain yang selaras dengan topik tulisan. Temuan penelitian ini ialah pembelajaran diferensiasi diimplementasikan melalui diferensiasi konten, proses, produk, dan lingkungan. Pengajaran, penilaian, dan aktivitas pembelajaran berdiferensiasi harus mengakomodasi keragaman gaya belajar, minat, dan tingkat kesiapan siswa. Pembelajaran berdiferensiasi efektif untuk diterapkan dalam pembelajaran. Pembelajaran berdiferensiasi berpengaruh positif dalam pembelajaran dari segi hasil belajar maupun proses belajar. Pembelajaran berdiferensiasi dapat meningkatkan prestasi akademik siswa, memberikan pengaruh positif terhadap motivasi, partisipasi, kemandirian, konsentrasi belajar, rasa percaya diri, dan pemahaman materi siswa.Kata Kunci: Efektivitas: Kurikulum Merdeka; pembelajaran berdiferensiasi; strategi